PENGEMBANGAN MODEL PEMBELAJARAN PERMAINAN BOLA BASKET MELALUI PENDEKATAN KERANJANG BERGERAK PADA SISWA PUTRI KELAS VII SMP NEGERI 1 BUARAN KABUPATEN PEKALONGAN TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
This study aims to produce a model of the game of basketball on class VII student daughter Secondary Schoolmore active, innovative and entertaining for students. The research was conducted at SMP N 1 Buaran,research development consists of planning, observation and action observation, and reflection. Data collectiontechniques in this study using the expert evaluation sheet used to collect data from experts and questionnaireswere used to collect data from expert and student evaluation. Test result data obtained by the expert evaluationdata, expert penjas 88.33% (excellent), learning experts I 95% (very good), a learning II 91.67% (excellent), asmall group of test results obtained questionnaires psychomotor aspects of 90.83%, 92.50% cognitive, andaffective 93.33%, of the overall results of the student questionnaire daughter small test group obtained apercentage of 92.22% (excellent), and a field test of psychomotor aspects of the questionnaire obtained 95 , 35%,97.74% cognitive, and affective 96.67%, the overall results of the field test questionnaire obtained a percentageof 96.59% (excellent). From the available data it can be concluded that the model of learning basketball cartmoves can be used for students of SMP N 1 Buaran Pekalongan.